THE EFFECTIVENESS OF Astaxanthin AND Spirulina sp ADMINISTRATION IN FEED ON COLOR QUALITY OF COMET FISH (Carassius auratus). - Margareta, Adelia; Isriansyah; Andi Nikhlani (Hasanuddin University, 2021)
ABSTRACT The purpose of this study was to analyze the effect of artificial feeding with the addition of a combination of Spirulina sp. and astaxanthin on the color quality of comet goldfish (Carassius auratus) seeds. The method used in this research was to apply a combination of dosages of Spirulina sp. and astaxanthin in artificial feed, namely 0% Spirulina sp.:0% Astaxanthin; 1% Spirulina sp.:0.1% Astaxanthin; 3% Spirulina sp.:0.1% Astaxanthin; and 5% Spirulina sp.:0.1% Astaxanthin. Experiments using a completely randomized design (CRD) consisted of four treatments and three replications, the color of the fish in each treatment was observed using a modified Toca Color Finder (TCF). The results of this study also indicate that the addition of 1% Spirulina sp. and 0.1% astaxanthin gave the best color to comet goldfish seeds. Keywords: Comet Goldfish, Astaxanthin, Spirulina sp., Color Quality, Growth